Pengaruh Pembelajaran Jarak Jauh (PJJ) Berbasis Google Classroom Terhadap Hasil Belajar Kognitif Peserta Didik Materi Ajar Biologi Kelas XI SMA Negeri 10 Sinjai - Nurfahsyai; St. Syamsudduha; Hamansah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to determine the effect of distance learning (PJJ) based on Google Classroom on students' cognitive learning outcomes. This study used a quantitative approach, and the population included all SMA Negeri 10 Sinjai students in class XI. Sampling was done by purposive sampling, with class XI MIPA 1 as the control and XI MIPA 2 as the experimental class. The instruments used were learning outcome tests and observation sheets. Data analysis included descriptive analysis and inferential analysis. The learning outcome in the experimental class has a mean of 52.06, while the control class has a mean of 77.83. Inferential analysis obtained a sig. value of 0.001, indicating that sig. a = 0.001 < 0.05, so H0 is rejected and H1 is accepted. These results indicate that distance learning (PJJ) based on Google Classroom affects the cognitive learning outcomes of biology teaching materials for class XI students at SMA Negeri 10 Sinjai.